2018
DOI: 10.1051/mfreview/2018013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multipoint cutting tool temperature using FEM and CFD

Abstract: Nimonic C-263 is a British nickel–chromium–cobalt–molybdenum alloy specially meant to be used in high-temperature and high-strength applications. Consequently, it produces high thermo-mechanical loads on the machining tool when machined. As a result, excessive heat is generated during dry drilling, between Nimonic C-263 and tungsten carbide tool coated with Alcorna, which in turn reduces the durability of the tool. In order to determine the temperature distribution of the tool, the coupling of finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Phoenics proves valuable in process engineering simulations, especially in modeling fluid flow and heat transfer in applications, such as airflow in buildings and HVAC systems [45][46][47], allowing steady-state and transient simulations. Acusolve efficiently handles large and complex simulations with parallel processing capabilities and various turbulence models to simulate turbulent flows accurately [48,49]. PAM-Flow, known for its robust capabilities, is ideal for simulating external aerodynamics, under-hood flows, and thermal management of vehicles [50].…”
Section: Commercial Software and Open-source Cfd Codesmentioning
confidence: 99%
“…Phoenics proves valuable in process engineering simulations, especially in modeling fluid flow and heat transfer in applications, such as airflow in buildings and HVAC systems [45][46][47], allowing steady-state and transient simulations. Acusolve efficiently handles large and complex simulations with parallel processing capabilities and various turbulence models to simulate turbulent flows accurately [48,49]. PAM-Flow, known for its robust capabilities, is ideal for simulating external aerodynamics, under-hood flows, and thermal management of vehicles [50].…”
Section: Commercial Software and Open-source Cfd Codesmentioning
confidence: 99%
“…To estimate the impacts of cutting fluid on the temperature of the tool during cutting operations, a coupling technique integrating computational fluid dynamics and finite element method is used [61].A computational and experimental research is provided to evaluate convective heat transfer and related cutting heat transfer in single point turning operations [62]. WC-Co cutting tools are subjected to FEM analysis to lower in-service temperature [63].Using FEM and CFD, a multipoint cutting tool temperature study is carried out to reduce the cutting temperature during the chip creation process [64].In order to reduce thermal errors during machining operations, heavy-duty CNC machine tool thermal error monitoring technology employing the fem technique is created [65]. In order to increase the precision of the mill head, thermal characteristics study of the mill head of a five-axis CNC mill machine based on finite element approach is implemented [66].A virtual machining software is developed to analyze and minimize cutting temperatures throughout milling operations of difficult-to-cut items [27].Figure 2 depicts the surface temperature throughout the milling simulation of the titanium alloy Ti6Al4V [27].…”
Section: Cutting Temperaturementioning
confidence: 99%
“…This process employed the usage of pareto optimal study and found the ultimate reduction of time by the meta-model based multi-objective optimization. In addition, the results paved way for future application of this method in drilling and other similar cutting processes [16]. Mohan et al used the simulative approach for the analysis of machining AISI 4340 with the support of Deform2D model.…”
Section: Introductionmentioning
confidence: 99%